PENINGKATAN PRODUKSI DAN PEMASARAN PADA USAHA RISOL MELALUI DIGITAL MARKETING - Suhartina Suhartina; Yuli Wahyu Tri Mulyani; Eka Ubaya Taruna Rauf (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Risol is a snack that has been known for so long. As a market snack, risol sold in the form of ready-to-eat already has a relatively stable market demand. Because risol is very popular from various circles, both ordinary people and office workers, for this reason, Nasi Goreng and Gorengan SMEs are also trying to develop their talents by opening a type of business